Quem escondeu o ritmo oculto? Um estudo de caso comparado entre o ritmo escolar no Brasil e França - Camargo, Rosa Maria Bortolotti de (2018)
The study was based on the term School Routine, understood as a curricular structure that leads the Formal, Legal and Implied school time operation.This paper aimed to analyze, based on a comparative study, how School Routine in Brazil and in France are manifested in the daily life of two public schools located in the low-income neighborhoods, one in each country. Data collection was made out based on a bibliographic-historical review of legal documents on the topic of the hours spent in school in Brazil and in France, participant observation and semi-structured interviews with teachers and monitors of two schools in the elementary school. The theoretical framework used were studies by authors that deal with the theme of the time children spent in school in Brazil, Jaqueline Moll (2012, 2013), Ana Cavaliere (2002, 2007, 2014), Miguel Arroyo (2012), in France, François Dubet (2012), Bernard Charlot (2002, 2013), Marie Pierre Chopin (2010), Bernard Lahire (1995) among others. Therefore, it was verified that the educational political debate about the time spent in school, in both countries, establishes a causal relationship between success or failure in school and social life, through the homogenization of the idea that the (re) organization, creation, improvement and qualification of the different times and school spaces are important factors to reduce the school inequalities and, consequently, the social ones, especially of the children who come from the lower classes. However, the study revealed a very different reality, leading to the conclusion that only the quantitative and formal change of the time spent in school is not in itself a solution for school failure, especially of the students who come from the lower classes. It is necessary that the new school times be qualified with educational spaces and with trainers engaged in education beyond the formal curriculum, that access to different activities must be the right of all children and adolescents who attend public schools and then, Finally, it is understood that in order to reform School Routines, it is fundamental not only to propose new extracurricular activities or more time in school, but also to understand that overcoming the traditional school model must be part of this change.